2022
DOI: 10.1177/11772719221132693
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Content of Ewing Sarcoma Derived Extracellular Vesicles Leads to Biomarker Potential and Identification of a Previously Undocumented EWS-FLI1 Translocation

Abstract: Objective: Ewing Sarcoma Family of Tumors (ESFT) are a highly aggressive pediatric bone and soft tissue malignancy with poor outcomes in the refractory and recurrent setting. Over 90% of Ewing Sarcoma (ES) tumors are driven by the pathognomonic EWS-ETS chimeric transcripts and their corresponding oncoproteins. It has been suggested that the EWS-ETS oncogenic action can mediate microRNA (miRNA) processing. Importantly, small extracellular vesicles (sEVs), including those frequently referred to as exosomes have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Using miRNA sequencing, Crow et al. ( 158 ) identified a disease-specific signature set of 62 exosomal miRNAs able to differentiate between ESFT and non-ESFT samples. Similarly, Kosela-Patercyzk et al.…”
Section: Mirna Biomarkers In Other Bone-related Diseasesmentioning
confidence: 99%
“…Using miRNA sequencing, Crow et al. ( 158 ) identified a disease-specific signature set of 62 exosomal miRNAs able to differentiate between ESFT and non-ESFT samples. Similarly, Kosela-Patercyzk et al.…”
Section: Mirna Biomarkers In Other Bone-related Diseasesmentioning
confidence: 99%
“…Additionally, the quantitative measurement of EWS-FLI1 mRNA copy numbers in pPNET-derived exosomes represents an effective biomarker signature with respect to total cell RNA content, increasing the sensitivity for MRD identification during therapy and post-therapy [ 86 ]. Analogously, ESFT patients have been proven to present a higher content of exosomal miRNAs, with an average of 275 exo-miRNAs identified in ESFT pediatric patients and <100 exo-miRNAs identified in pediatric non-cancer, rhabdomyosarcoma, and OS samples [ 87 ]. Of note, Pearson’s clustering of 46 exo-miRNAs correctly identified 80% (4 of 5) of pathology-confirmed ESFT patients, with respect to healthy controls and 75% (3/4) of the non-ESFT sarcoma samples [ 87 ].…”
Section: Clinical Utility Of Exosomes Detection In Liquid Biopsymentioning
confidence: 99%
“…Analogously, ESFT patients have been proven to present a higher content of exosomal miRNAs, with an average of 275 exo-miRNAs identified in ESFT pediatric patients and <100 exo-miRNAs identified in pediatric non-cancer, rhabdomyosarcoma, and OS samples [ 87 ]. Of note, Pearson’s clustering of 46 exo-miRNAs correctly identified 80% (4 of 5) of pathology-confirmed ESFT patients, with respect to healthy controls and 75% (3/4) of the non-ESFT sarcoma samples [ 87 ]. Importantly, RNAseq analysis of tumor tissue from the one outlier revealed a previously uncharacterized EWS-FLI1 translocation [ 87 ].…”
Section: Clinical Utility Of Exosomes Detection In Liquid Biopsymentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, EWS derived sEVs have been shown to mediate cross-talk with the surrounding tumor microenvironment and promote immunosuppressive phenotypes (Gassmann et al, 2021;Pachva et al, 2021). We have recently reported that circulating sEVs can be used to accurately diagnose EWS patients using a panel of exo-miRNAs (Crow et al, 2022). sEVs have great potential to be explored as biomarkers to detect early-stage cancers and also monitor tumor progression and predict outcomes (Xu et al, 2018;Möller and Lobb, 2020).…”
Section: Introductionmentioning
confidence: 99%